Incidence and risk factors of phlebitis among adult patients with peripheral intravenous catheter - Daud, Azlina; Mohamad, Fatimah (2018)
The insertion of peripheral intravenous catheter (PIVC) is essential among hospitalized patients for treatment purposes. However, this procedure usually fails before the end of therapy due to many complications. One of the most complications occurred is phlebitis. Therefore, this study aims to determine the incidence rate of phlebitis among patients with PIVC and the factors associated with phlebitis. There were 161 data collected among patients who had PIVC in medical, gynecology and orthopedic wards. The incidence of phlebitis was evaluated using modified Visual Infusion Phlebitis (VIP) score checklist. The incidence of phlebitis, is 32.3% (n=52). The associated factors that contributed to the incidence of phlebitis in this study were present of chronic disease and patients with history of phlebitis (p<0.05). Overall, phlebitis was the most frequent reason of PIVC removal and complication in this study. This high incidence from the result indicated a worrying outcome. This study demonstrated that patients with chronic disease and history of phlebitis were most likely to develop phlebitis.